On the application of weld strength factors on welded components. (31st May 2011) - Bauer, Mathias; Klenk, Andreas; Maile, Karl; Roos, Eberhard
One way of describing the material behaviour of welded components is the implementation of weld strength factors in the design process or life assessments. In general, this factor neither takes the influence of the complex, multiaxial stress situation in large components into account, nor relaxation or constraint effects. In the research presented here, numerical finite element simulations using inelastic constitutive equations – offering the possibility to characterise the influence of the stress distribution and degree of multiaxiality in the weld region – are used to obtain a more detailed interpretation of reduced weld strength. Different weld geometries are investigated by finite element analysis with regard to evaluate the influence of the weld on the overall component behaviour. The results show, that the transferability of small scale material properties and in particular the weld strength factor to thick walled parts based on analytical methods is difficult and may not be an appropriate tool for the design of welded components.